Art and the Challenge of Markets Volume 2 From Commodification of Art to Artistic Critiques of Capitalism (Sociology of the Arts ,, 2018)
Art and the Challenge of Markets Volumes 1 & 2 examine the politics of art and culture in light of the profound changes that have taken place in the world order since the 1980s and 1990s. The contributors explore how in these two decades, the neoliberal or market-based model of capitalism started to spread from the economic realm to other areas of society. As a result, many aspects of contemporary Western societies increasingly function in the same way as the private enterprise sector under traditional market capitalism. This second volume analyses the relationships of art with contemporary capitalist economies and instrumentalist cultural policies, and examines several varieties of capitalist-critical and alternative art forms that exist in today's art worlds. It also addresses the vexed issues of art controversies and censorship. The chapters cover issues such as the culturalization of the economy, aesthetics and anti-aesthetics, the societal benefits of works of art, art's responsibility to society, "artivism", activist arts as protest and capitalism-critical works, and controversies over nudity in art, as well as considering the marketisation of emerging visual arts worlds in East Asia. The book ends with the a concluding chapter suggesting that even in today's marketized and commercialized environments, art will find a way. Both volumes provide students and scholars across a range of disciplines with an incisive, comparative overview of the politics of art and culture and national, international and transnational art worlds in contemporary capitalism.